Determination of Gestational Age: A Perspective With the Bangladeshi Ethnicity - Rahman, M. Lutfor; Sultana, Aysha; Das, Kalyan (European Scientific Journal, ESJ, 2018)
Determination of gestational age (GA) with precision is vital to the proper care of pregnant mothers. Our present study aimed at determining the gestational ages by the ultrasonic measurements of four standard fetal parameters namely biparietal diameter (BPD), head circumference (HC), abdominal circumference (AC), and femur length (FL) specifically focusing on the Bangladeshi ethnic population. The current study is cross-sectional but data were collected in a prospective nature. There were 229 Bangladeshi women who had usual singleton fetuses with the evidence of menstrual dates by sonography before 14 weeks. Fetal anatomical structures have been scanned and measured at the time of sonographic inspection. Multiple linear regression models of GA by the date of last menstrual period (LMP) and GA by ultrasonographic measures have been fitted on four fetal parameters for our analysis. In the present analysis, we have found that all the response variables i.e. gestational age by LMP and gestational age by ultrasonography (USG) clearly depend on the fetal parameters. The best subsets regression analysis shows that BPD, AC, and FL are the best predictors of GA by LMP (adj R 2 = 96.54). In terms of Mallow’s Cp and adj R 2 , it is found that all the fetal parameters BPD, AC, HC and FL are important predictors for GA by USG. It has been observed that multiple fetal parameters measured by ultrasonography can be useful to predict gestational age during second and third trimesters. Precise estimation of gestational age by this method is helpful to reduce pregnancy-related complicacy and maternal death in the developing countries including Bangladesh.